Evaluación de la eficiencia de precipitación de los alcaloides procedentes del lupinus mutabilis sweet por el método de mayer en la Universidad Técnica de Cotopaxi Campus Salache período 2021 – 2022. - Bastidas Tello, María Ximena (2022)
Lupinus mutabilis Sweet is a legume with great nutritional, productive and pharmacological potential; however, the beneficial nutritional benefits that lupin seeds offers are limited in its direct use for humans and animals by substances such as alkaloids, which give the seed a bitter taste and toxic character. The traditional debittering process is commonly carried out in irrigation ditches or rivers, contributing to water degradation, environmental pollution and waste of these residual effluents, rich in alkaloids. Therefore, the precipitation efficiency of alkaloids from Lupinus mutabilis Sweet in the dewatering water was evaluated using Mayer's method. Then, a multifactorial experimental design with three factors and three levels was executed. Then, the quantification of quinolizidines established a maximum precipitate of 87.60% in two treatments (T1-120rpm-XXX, T2-120rp-XXX) and a minimum of 80.16% for T1-90-XV, highlighting the influence of the shaker at 120 rpm during a period of 30 minutes. These results, contrasted with the statistical significance (95% confidence level) for treatments A, B and C, made it possible to determine a high efficiency in removing alkaloids in a range greater than 70%. In addition, the appropriate conditions for a higher precipitation efficiency were established, consisting of the application of 0.7 mL, 30 minutes and 120 revolutions per minute (rpm), for the factors of mayer's reagent concentration, agitation time and agitation speed, respectively. Finally, there was a direct influence of the factors time and stirring speed on alkaloid precipitation.